The Analysis of Pedagogical Competence of The English Teachers’ of The Third Grade Students at SMA Negeri 3 Banda Aceh - Rosdiana Rosdiana (Edunesia: Jurnal Ilmiah Pendidikan, 2020)
Abstract: This research tries to analyze the teacher’s pedagogical competence in Teaching English. There are six pedagogical competence that need to be mastered by a teacher. They are understanding the subject in English lesson, the ability in understanding the students, the ability in setting and implementing lesson plan and learning strategy, the ability in creating educational and dialogical learning which is interactive, utilizing the learning technology, and evaluating the learning outcomes. Thus, this research focus on the teacher’s pedagogical competence that consist of the six components. This research uses a descriptive qualitative approach and the researcher used observation, questionnaire, and document analysis as the method of collecting data. The objective of this research is to know whether the English teacher has all components in pedagogical competence and to know the students’ perpective on the teacher’s pedagogical competence. The result of research is the English teacher has all of the components of the pedagogical competence. Based on the observation, documentation analysis, and the data of questinnaire shows that the English teacher has the abilty in understanding the subject in English lesson, the ability in understanding the students, the ability in setting and implementing lesson plan and learning strategy, the ability in creating educational and dialogical learning which is interactive, utilizing the learning technology, and evaluating the learning outcomes. . Abstrak: Penelitian ini mencoba menganalisis kompetensi pedagogik guru dalam Pengajaran Bahasa Inggris. Ada enam kompetensi pedagogik yang perlu dikuasai oleh seorang guru. Mereka memahami subjek dalam pelajaran bahasa Inggris, kemampuan dalam memahami siswa, kemampuan dalam menetapkan dan menerapkan rencana pelajaran dan strategi pembelajaran, kemampuan dalam menciptakan pembelajaran pendidikan dan dialogis yang interaktif, memanfaatkan teknologi pembelajaran, dan mengevaluasi hasil pembelajaran . Dengan demikian, penelitian ini fokus pada kompetensi pedagogik guru yang terdiri dari enam komponen. Penelitian ini menggunakan pendekatan kualitatif deskriptif dan peneliti menggunakan observasi, kuesioner, dan analisis dokumen sebagai metode pengumpulan data. Tujuan dari penelitian ini adalah untuk mengetahui apakah guru bahasa Inggris memiliki semua komponen dalam kompetensi pedagogis dan untuk mengetahui perspektif siswa tentang kompetensi pedagogis guru. Hasil penelitian adalah guru bahasa Inggris memiliki semua komponen kompetensi pedagogis. Berdasarkan pengamatan, analisis dokumentasi, dan data kuesioner menunjukkan bahwa guru bahasa Inggris memiliki kemampuan dalam memahami subjek dalam pelajaran bahasa Inggris, kemampuan dalam memahami siswa, kemampuan dalam menetapkan dan menerapkan rencana pelajaran dan strategi pembelajaran, kemampuan dalam menciptakan pembelajaran pendidikan dan dialogis yang interaktif, memanfaatkan teknologi pembelajaran, dan mengevaluasi hasil pembelajaran